Avaliação da utilização de válvulas pneumáticas de retenção pilotada em sistemas de posicionamento eletromecânico - Michatowski, Roberto Carlos (2017)
The use of pneumatic actuators represents low-cost and high-reliability solutions for industrial automated systems. However, the physical characteristics of compressed air make it difficult and sometimes impossible to use such actuators in situations demanding positioning with good accuracy. Standing out as unfavorable factors are the lack of pressure linearity, which is caused by the compressibility of air, and the behavior of the actuators' inner seal. In light of this restricting condition of pneumatic actuators, electromechanical hydraulic actuators are usually used, considering they provide better conditions for positioning with good accuracy. However, these systems not only represent a rather higher cost, but also present less favorable characteristics regarding maintenance and weight/power ratio. Seeking for new alternatives, this work presents an experimental theoretical study on a positioning control system of a pneumatic actuator using piloted check valves, aiming to assess the applicability of such valves on electromechanical positioning systems. A circuit model with piloted check valves was proposed and motion tests were developed under different load and speed conditions along with two other conventional circuit models, aiming to measure the positioning accuracy of each circuit for comparison. Data on positioning readings were collected and later assessed through statistical analysis. The analysis of variance results indicated that the circuit proposed with piloted check valves, which was the focus of this study, presented positioning average error significantly lower than the other circuits. The positioning accuracy obtained was in the order of 0.08 mm, which in practice represents an excellent degree of accuracy, comparable to that obtained in hydraulic and electromechanical positioning systems. The results obtained positively recommended the application of piloted check valves on electromechanical positioning systems, thus highlighting it as a favorable alternative to conventional pneumatic actuation systems in applications which work conditions are within the load and speed rates analyzed in this work.